2021
DOI: 10.3389/fped.2021.583660
|View full text |Cite
|
Sign up to set email alerts
|

Protective Factors for Early Childhood Caries in 3-Year-Old Children in Poland

Abstract: Background: Early childhood caries (ECC) remains highly prevalent in preschool children worldwide. Dental caries affects every second 3-year-olds in Poland. The aim of the study was to assess protective factors for ECC in 3-year-olds.Methods: A cross-sectional survey was conducted in 2017 among 3-year-olds attending kindergartens in all 16 provinces of Poland. The questionnaire included socioeconomic factors, and oral health behaviors. Decayed, missing due to caries and filled teeth and surfaces were assessed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 35 publications
1
34
1
Order By: Relevance
“…Diet plays a particularly important role in the etiology of early childhood caries. Olczak-Kowalczyk et al [41] revealed that an effective way to reduce the risk of caries development at the age of 3 is appropriate nutritional management starting from the age of 12 months. The child should only drink water or unsweetened milk, and sugar-free snacks and fruit may be served between meals.…”
Section: Discussionmentioning
confidence: 99%
“…Diet plays a particularly important role in the etiology of early childhood caries. Olczak-Kowalczyk et al [41] revealed that an effective way to reduce the risk of caries development at the age of 3 is appropriate nutritional management starting from the age of 12 months. The child should only drink water or unsweetened milk, and sugar-free snacks and fruit may be served between meals.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier birth cohort from this city also reported a significant association between low maternal prenatal 25(OH)D concentrations and ECC [10], and even found that prenatal calcium levels and enamel hypoplasia are significantly associated [24]. However, a recent Polish study investigating the relationship between parental reported vitamin D supplementation and caries did not identify a significant relationship [25].…”
Section: Discussionmentioning
confidence: 99%
“…There are significant differences in oral health between members of different European Union states, with a markedly worse epidemiological situation in a few Eastern and Central European countries [ 1 , 5 , 6 , 7 , 8 , 9 ]. The oral health of Polish preschoolers is much worse than that of preschoolers in most other European countries [ 5 , 6 , 10 ]. According to reports from national oral health monitoring programmes commissioned by the Ministry of Health for the years 2016–2020, the prevalence of dental caries increases substantially with age from 41.1% in 3-year-olds to 85.1% in 7-year-olds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that caries and its complications may severely impact general health and quality of life [ 1 , 5 , 6 , 7 , 10 ]. However, this disease and its negative consequences can be prevented to a large extent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation